Peran kecintaan merek terhadap kepuasan merek, keterlibatan merek, dan loyalitas merek - Burhanudin Burhanudin; Binta Febryanti (Jurnal Manajemen Maranatha, 2023)
This research aims to examine the influence of brand satisfaction on brand love and subsequently on both brand engagement and brand loyalty in the context of beauty products. Additionally, this research examines the mediation effect of brand love on the relationship between brand satisfaction and brand engagement, as well as between brand satisfaction and brand loyalty. The sample for this research consisted of 358 respondents. This study employed structural equation modeling to analyze the data. The results of this research indicate that brand satisfaction has a significant positive effect on brand love and subsequently on both brand engagement and brand loyalty. Additionally, this research reveals mediation effects, with brand love mediating the relationship between brand satisfaction and brand engagement, as well as between brand satisfaction and brand loyalty. These findings suggest that beauty product marketers can utilize brand satisfaction to drive engagement, loyalty, and love to a brand as a marketing strategy.